2014
DOI: 10.1371/journal.pone.0084233
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Multiple Enteroviruses Associated with Hand, Foot, and Mouth Disease in Shijiazhuang City, Hebei Province, China: Outbreaks of Coxsackieviruses A10 and B3

Abstract: Hand, foot, and mouth disease (HFMD) has been one of the most common infectious diseases in Shijiazhuang City, as is the situation in China overall. In the National HFMD surveillance system, the pathogen detection was focused on EV-A71 and CVA16, and therefore, information on the other EVs is very limited. In order to identify the circulating EV serotypes in the HFMD outbreaks in Shijiazhuang City during 2010–2012, 4045 patients presented with HFMD were recruited in the study, and clinical samples were investi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
70
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 66 publications
(73 citation statements)
references
References 18 publications
3
70
0
Order By: Relevance
“…The results showed that EV71 and CVA16 were still the two major pathogens (33). In the evaluation, all the positive samples by our new approaches also tested positive by the corresponding qRT-PCRs.…”
Section: Discussionmentioning
confidence: 85%
“…The results showed that EV71 and CVA16 were still the two major pathogens (33). In the evaluation, all the positive samples by our new approaches also tested positive by the corresponding qRT-PCRs.…”
Section: Discussionmentioning
confidence: 85%
“…EV-A71 and CV-A16 were responsible for 90.2% and 8.7% of fatal outcomes, respectively. 17,24,29,31,40,41,44,47,49,58,67 Although usually mild, CV-A16 infection may lead to neural and muscle cells apoptosis 118 and has occasionally been the cause of rhombencephalitis, brain stem encephalitis and acute flaccid paralysis, fatal pneumonitis and fulminant myocarditis with intractable shock. 8 Since 2004, the incidence of CV-A6-and CV-A10-associated HFMD epidemics has markedly increased worldwide [ Table 1].…”
Section: Enteroviruses Cell and Tissue Tropismmentioning
confidence: 99%
“…Co-circulating CV-A10 strains isolated during the epidemic in the Hebei province between 2008 and 2012 were found to segregate into 4 clusters (A-D), the C genotype being further divided into 4 lineages. 24 All Chinese CV-A10 segregated into the B and C genotypes, genotype B in Shangdong and genotype C in the other provinces. Another phylogenetic analysis of CV-A10 strains indicated that they cluster into 7 genotypes (A to G).…”
Section: Molecular Epidemiologymentioning
confidence: 99%
See 2 more Smart Citations